The Determinants of Fiscal Deficit in South Africa: A Bayesian Vector Autoregressive Approach - Kasongo, Atoko (International Journal of Economics and Financial Issues, 2023)
This study empirically investigates the factors influencing South Africa’s fiscal deficit from 1975 to 2021. The research design used the Bayesian vector autoregressive estimation with the Minestor prior. The findings are analysed using the impulse response function and variance decomposition. The findings revealed that government debt, GDP growth, money supply, and interest rate as determinants of the fiscal deficit. Impulse response functions showed positive and significant impacts of government debt on the fiscal deficit; negative and significant impacts of economic growth, money supply, and interest rate on fiscal deficits. The variance decomposition showed that economic growth and national debt explained the variations in fiscal deficit in the long run. The relationship between macroeconomic factors and fiscal deficit could have social consequences for the even distribution of resources, equitable growth, and overall welfare. This study contributes to the limited literature on the macroeconomic determinants of fiscal deficit in the South African economy and Africa at large.